Strategy For Management of the Soenda Ketjil Museum As A Tourism Attraction in Singaraja City, Bali - Frika Yanuar Ramadhani; I Wayan Srijaya; Coleta Palupi Titasari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Soenda Ketjil Museum is one of the museums that is used as a tourist attraction in Singaraja City, Buleleng Regency, Bali. By seeing the importance of the role of museums in this era, the authors are interested in discussing management strategies and the potential of the Soenda Ketjil museum as a tourist attraction in the city of Singaraja, Bali. This study aims to maximize the potential and management of the Soenda Ketjil Museum, so that it can make the Soenda Ketjil Museum an attractive place for the public to visit. This research uses structural functional theory and management theory. The data collection method used is the method of observation, literature study, and interviews. The data analysis technique used is qualitative analysis and SWOT analysis. Soenda Ketjil Museum has internal potential and external potential. The internal potential of the Soenda Ketjil Museum consists of the collection and storyline it owns, the museum building, and the audiovisual room of the Soenda Ketjil Museum. Its external potential is the strategic location of the Soenda Ketjil Museum, and the existence of other supporting tours that can support the existence of the Soenda Ketjil Museum. To achieve the goals of the Soenda Ketjil Museum as a tourist attraction, it is formulated as follows: revamping the organizational structure of the museum, increasing human resources, improving the museum's security system, improving the management of museum collections, restoring the function of the audiovisual room, and revamping the facilities in the museum.